EVALUATION OF HEPATOPROTECTIVE POTENTIAL OF LEAF AND LEAF CALLUS EXTRACTS OF ANISOCHILUS CARNOSUS (L) WALL. - Nissar Ahmad Reshi; Sudarahana Mysore Shankarsingh; Girish Hodiyala Vasanaika (International Journal of Phytomedicine, 2018)
The study was carried out to evaluate the hepatoprotective activity of leaf and leaf callus extracts of Anisochilus carnosus (L) Wall. against alcohol induced toxicity using HepG2 cell line. Leaf explants were cultured on Murashige and Skoog solid medium supplemented with different growth regulators. Prior to the determination of hepatoprotective property leaf and leaf callus extracts were subjected to the toxic dose study. The degree of hepatoprotection of extracts was determined by measuring cell viability percentage by MTT assay. The preliminary phytochemical analysis of leaf and leaf callus was carried out by qualitative analysis. Maximum percentage of callus formation (98%) was obtained in MS medium fortified with 3 mg/l 2,4-D. HepG2 cells were pretreated with the different concentrations (below toxic dose) of leaf and leaf callus extracts for 72 hours followed by alcohol intoxication. Results revealed that ethanolic leaf extract pretreated HepG2 cells show 94% cell viability compared to the standard silymarin pretreated HepG2 cells which showed 81% cell viability. Leaf callus extracts also exhibited significant hepatoprotective activity where ethanolic callus extract pretreated HepG2 cells showed 86% viability after intoxication with alcohol. Results revealed that HepG2 cell viability percentage is dose dependent. Phytochemical studies revealed the presence of different secondary metabolites in leaf and leaf callus extracts. The bio-efficacy study confirms the presence of secondary metabolites of hepatoprotective nature in leaf and leaf callus of A. carnosus.